The Function of Emotional Intelligence and Motivation to Improve the Speaking Skills of the Students - ardiyanti, Lina; Mujiyanto, Januarius; Wahyuni, Sri (English Education Journal, 2023)
Student learning success can be seen from the learning results obtained after participating in the lesson. Several factors, including emotional intelligence and motivation, can influence learning outcomes. Students who have good emotional intelligence and motivation will influence the learning outcomes obtained. This research aims to determine the influence of emotional intelligence and motivation on the speaking skills results of class XI students at SMAN 3 Bojonegoro. This research uses a quantitative approach. The population in this study was class XI students at SMAN 3 Bojonegoro, totaling 126 students with a research sample of 96 students. The data analysis method for this research includes prerequisite analysis tests consisting of normality, linearity, multicollinearity and heteroscedasticity tests, as well as a final analysis consisting of simple correlation analysis and simple regression analysis. Speaking skills t-count > t-table (4.072 > 1.985), meaning H0 is rejected. The hypothesis test results on the influence of motivation on students' speaking results, t-count > t-table (3.420 > 1.985), means that H0 is rejected. The hypothesis test results on the influence of emotional intelligence and motivation on speaking skills together obtained Fcount > Ftable (10.929 > 3.094), meaning H0 was rejected. Hypothesis test results of the relationship between emotional intelligence and motivation r-count > r-table (0.436 > 0.190), meaning H0 is rejected. The findings of this research indicate that enhancing students' speaking skills necessitates emotional intelligence and motivation. These factors drive students to engage in learning and guide their learning activities, ultimately maximizing learning outcomes.